Recent progress in nano-oxides and CNTs based corrosion resistant superhydrophobic coatings: A critical review - Sharma V.; Goyat M.S.; Hooda A.; Pandey J.K.; Kumar A.; Gupta R.; Upadhyay A.K.; Prakash R.; Kirabira J.B.; Mandal P.; Bhargav P.K. (My University, 2025)
Because of the serious consequences of structural failures due to corrosion, research on anti-corrosion coatings has traditionally been of highest importance toward the development of sustainable durable material. Anti-corrosive coatings have played a significant role for increasing the durability of material without affecting the bulk properties and to perform its duty effectively, an anti-corrosive coating must possess intrinsic durability, adequate flexibility, adhesion and toughness to withstand impacts, cracking and appearance when subjected to stress, swell, mechanical abuse, or weathering. Exposure of metals and alloys in a humid environment may create additional challenges either to inhibit or slow down the overall corrosion rate. Despite significant improvements in corrosion coating technologies problems are continue to persist in the durable protection of metals and alloys and this is an emerging thrust area toward the development of a holistic, permanent solution for the corrosion related issues. In recent years, bio-inspired concepts of superhydrophobicity at nano-level and self-cleaning has exhibited exceptional potential as anticorrosive coatings, particularly in humid environments. With the ability to retain mechanical properties at a higher temperature and contact angle (CA) of superhydrophobic range, nano-oxides and CNTs based superhydrophobic coatings (SHCs) are gaining momentum to reach an industrial scale for real-time applications. The present article is mainly aimed to review the impact of nano-material based SHCs on metal/alloys with a concise discussion of associated challenges, potential solutions and future opportunities. © 2019 Elsevier B.V.